Desenvolvimento e construção de um fantoma homegêneo de mão para otimização de imagens radiográficas - Pavan, Ana Luiza Menegatti [UNESP] (2014)
Computed Radiology (CR) has been widely used to assist medical diagnosis in hospitals and clinics worldwide. However clinical routine commonly use charts of techniques used in screen-film systems to obtain images in the detection CR systems. The international standards already established parameters of quality control tests in CR. However the national normative work for this construction. Recent studies suggest methods for optimizing images on CR systems for skull, pelvis and thorax exams for adult standard patients without reporting the exams of hand. Many diseases affecting hands today use the X-ray examination as an aid to diagnosis. It is noteworthy that the technique should provide images with maximum possible information for a safety diagnosis, with the lowest dose to the patient, and cost savings to the institution where the exams are performed. In this study a homogeneous phantom hand was developed to be used in the optimization of hand images using CR system. In this procedure were quantified thicknesses of different tissues that constitute an anthropomorphic phantom hand from CT scans. The same procedure was adopted for retrospective examinations of 30 patients of the Hospital das Clinicas, of School Medicine of Botucatu, UNESP (HCFMB-UNESP). The results showed agreement between the thicknesses of tissues that constitute the anthropomorphic phantom and sampling of patients, presenting variations between 12.63% and 6.48% for soft tissue and bone, respectively. The homogeneous phantom was used in the calibration of the X-ray beam process, producing tests technical. These techniques were applied in an anthropomorphic phantom hand from CT scans. The same procedure was adoped for retrospective examinations of 30 patients of the Hospital das Clinicas, of School Medicine of Botucatu, UNESP (HCFMB-UNESP). The results showed agreement between the thicknesses of tissues that constitute the anthropomorphic phantom and sampling of ...